Efektivitas Metode Simak-Respons dalam Meningkatkan Hasil Belajar Menyimak pada Siswa SMP Kelas VII - Rahma Amalia; Intan Nabila Azahra; Silmi Aulia Nurul Qolbi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study explores how a digital-based listen–response method—combining vibrant video stimuli with instant, game-like feedback on the Quizizz platform—can transform listening comprehension from a passive task into an energizing adventure. Involving 39 junior high students, the research gathered performance data from structured listening quizzes and direct teacher observations. With an impressive average score of 87.17—most students achieving “Good” to “Excellent” levels—and vivid improvements in focus and enthusiasm, the findings reveal that turning listening exercises into interactive challenges boosts both comprehension and motivation. Yet, to master higher-order inferential skills, follow-up discussions and reflection activities are essential. By harnessing this method, educators can reimagine listening lessons as interactive journeys that captivate learners and deepen their language skills.